Microstrip Compact Twin-Interdigital Steped Impedance Resonator-Based Bandpass Filter for C-Band Applications - Maharjan, Ram Krishna (Journal of Advanced College of Engineering and Management, 2018)
This research focuses a new microstrip twin-interdigital type bandpass filter based on stepped impedance resonator (SIR) structure. The proposed structure consists of two slightly different interdigital capacitances within a single SIR resonator that behaves as a bandpass filter (BPF) of center frequency 4.3 GHz with 700 MHz bandwidth at 3 dB pass band. This design is not only subjected to size reduction, but also low pass-band insertion loss and high return loss as well. The Sonnet software tool has been used to design and simulate the microstrip BPF. The fabricated BPF was measured using the Agilent 8510C vector network analyzer (VNA) and achieved the insertion loss of 0.5 dB and the return loss of 26 dB. The measured results were compared with those simulated results which were very close to each other. The fabricated BPF can be used for Cband Applications.